Perinatal and social risk of poor language, memory, and learning outcomes in a cohort of extremely and very preterm children - Valois, R (2022)
Children born extremely preterm (EPT) or very preterm (VPT) are at risk of neurodevelopmental impairment. How the interaction between biological and social risk factors affects cognitive development has not yet been completely understood. The objectives of this study are to analyze and compare the language, memory, and learning outcomes of five-year-old children born EPT (<28 weeks’ gestational age) and VPT (28–31+6 weeks’ gestational age) and to determine the risk of having poor outcomes attending to perinatal and maternal characteristics. The analysis included 377 children born VPT (n = 284) and EPT (n = 93) in 2011–2012. Maternal, neonatal, and clinical information was obtained at birth, and maternal education was obtained at five years using a parental questionnaire. At five years, the language, memory, and learning outcomes were assessed with the developmental NEuroPSYchological assessment second edition (NEPSY-II®). Logistic regression models were applied to assess the association of biological and social risk factors with performance below the expected level for the child’s age in language, memory, and learning subtests. Lower maternal age and education increased the odds of having language performance below the expected level for the child’s age, while lower maternal educational level and gestational age increased the likelihood of having memory performance below the expected level. Children living in the most social disadvantage contexts are at a higher risk of suboptimal cognitive development. Implementing intervention programs in disadvantaged contexts and targeting specific cognitive domains may enable EPT and VPT children to reach and fulfill their potential in society. © 2022 Informa UK Limited, trading as Taylor & Francis Group.